Alagille syndrome and risk for hepatocellular carcinoma: Need for increased surveillance in adults with mild liver phenotypes. Issue 3 (24th December 2020) - Schindler, Emma A.; Gilbert, Melissa A.; Piccoli, David A.; Spinner, Nancy B.; Krantz, Ian D.; Loomes, Kathleen M.
Abstract: Alagille syndrome (ALGS) is a multisystem autosomal dominant developmental disorder caused predominantly by pathogenic variants in JAGGED1 ( JAG1 ), and also by pathogenic variants in NOTCH2 in a much smaller number of individuals. Clinical presentation is highly variable and includes liver, heart, eye, skeleton, and facial abnormalities, with a subset of individuals also presenting with kidney, vascular, and central nervous system phenotypes. Hepatocellular carcinoma (HCC) is a rare complication of ALGS, though little is known about its incidence or etiology among affected individuals. Previous reports have identified HCC occurrence in both pediatric and adult cases of ALGS. We present a case report of HCC in a 58‐year‐old woman with a pathogenic JAG1 variant and no overt hepatic features of ALGS. Through a comprehensive literature review, we compile all reported pediatric and adult cases, and further highlight one previously reported case of HCC onset in an adult ALGS patient without any hepatic disease features, similar to our own described patient. Our case report and literature review suggest that ALGS‐causing variants could confer risk for developing HCC regardless of phenotypic severity and highlight a need for a cancer screening protocol that would enable early detection and treatment in this at‐risk population.